THE INFLUENCE OF USING COMICS STRIPS IN TELLING STORIES AND STUDENTS’ LEARNING MOTIVATION TOWARD THE READING ABILITY OF THE EIGHTH GRADE STUDENTS AT SMPI MARYAM MURAIT MARTAPURA - Murti Sari Dewi (Esteem Journal of English Education Study Programme, 2022)
The objective of this study is to find out whether or not there is any significant effect on the eight grade students’ learning motivation toward the reading ability after being taught by using comics strips. The population of  this  study was the eight grade students at SMPI Maryam MuraitMartapura in academic 2021/2022. The total number of the population was 142 students, The sample was consisted of 36 students of R1 and 36 students of R2. The method of the study was the experimental method and the data were  collected  through  written  test  in  multiple  choice  form.  The test was administrated twice as the pre-test and post-test. The result were analyzed by using t-test. The students’ Mean score of pretest and post-test in control class of R1 were 46.11 and 6,67. While  the  students’ Mean score  of  Pretest and post  test  in  experimental class of  R2 were 46,67 and 5,56.  The  null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.